Culture & Electronic Word-of-Mouth : A Case Study of the Hotel Industry in the Northern Sweden - Nilsson, Saga; Vennberg, Karin (2016)
Word-of-mouth has been a part of individuals’ lives since humans began to engage in oral communication, and is seen as powerful marketing tool. However, in the contemporary marketplace word-of-mouth marketing has evolved into electronic word-of-mouth (eWOM). This has given both marketers and consumers new possibilities to share information with each other as people have become active participants of eWOM. Consumers now share both positive and negative comments about experiences of products and companies, that in turn, functions as references for prospective customers and can damage or enhance the organisation's reputation. Furthermore, as a result of globalisation people are travelling around the world and this has led to an increasing interest in cultural differences and its effect on organisations. Travellers often check reviews before they make a reservation for accommodation and this have great implications for organisations in the hotel industry. However, there is not a shared understanding of how eWOM vary, strategies that are appropriate to use or how to adapt to cultural differences. Hence, the purpose of this thesis is to provide a better understanding on how cultural dimensions’ influence organisations' eWOM strategy.For this thesis, a case study of two hotels in northern Sweden was conducted and two managers responsible for their eWOM communication were interviewed. The findings from the case studies suggests that hotels distribute their attention to eWOM unevenly and adapt their communication to different cultural contexts poorly. Validerat; 20160822 (global_studentproject_submitter)